The Micro-Foundations of Public Service Reform: Transformational Leadership in Setu Urban Village, East Jakarta - Sulisti Nabilah Fatin; Dadan Kurniansyah; Kariena Febriantin (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
Public service reform at the urban-village level remains constrained by procedural rigidity, limited administrative capacity, uneven digital readiness, and the gap between formal service standards and citizens’ everyday service experiences. This article aims to analyze how transformational leadership functions as a micro-foundation of public service reform in Setu Urban Village, East Jakarta. Using a qualitative single-case study design, data were collected through semi-structured interviews, direct observation, and document analysis involving urban-village officials, frontline service officers, community representatives, and residents. The findings reveal that the Lurah’s transformational leadership was manifested through exemplary discipline, integrity, motivational communication, participatory coordination, intellectual stimulation, and individualized staff support. These practices contributed to stronger service readiness, improved internal coordination, adaptive digital service assistance, community outreach, and more citizen-oriented service behavior. The study implies that public service reform is not produced solely by formal procedures or digital systems, but also by everyday leadership mechanisms that shape frontline bureaucratic behavior. Sustainable reform therefore requires institutionalizing leadership-driven practices into service standards, staff capacity development, feedback systems, and accountability mechanisms.